Tyrosine hydroxylase and β2-adrenergic receptor expression in leukocytes of spontaneously hypertensive rats: putative peripheral markers of central sympathetic activity - Nisimura,L.M. (2020)
The sympathetic nervous system (SNS) plays a fundamental role in the pathophysiology of cardiovascular diseases, including primary arterial hypertension. In this study, we aimed to investigate whether the expression of the rate-limiting enzyme in catecholamine synthesis, tyrosine hydroxylase (TH), and the β2-adrenergic receptor (β2-AR) in immune cells from peripheral blood, reflect central SNS activity in spontaneously hypertensive rats (SHR). TH expression in the lower brainstem and adrenal glands and β2-AR expression in the lower brainstem were analyzed by western blot analyses. In the leukocytes, TH and β2-AR expression was evaluated by flow cytometry before and after chronic treatment with the centrally-acting sympathoinhibitory drug clonidine. Western blot analyses showed increased TH and β2-AR expression in the lower brainstem and increased TH in adrenal glands from SHR compared to normotensive Wistar Kyoto rats (WKY). Lower brainstem from SHR treated with clonidine presented reduced TH and β2-AR levels, and adrenal glands had decreased TH expression compared to SHR treated with vehicle. Flow cytometry showed that the percentage of leukocytes that express β2-AR is higher in SHR than in WKY. However, the percentage of leukocytes that expressed TH was higher in WKY than in SHR. Moreover, chronic treatment with clonidine normalized the levels of TH and β2-AR in leukocytes from SHR to similar levels of those of WKY. Our study demonstrated that the percentage of leukocytes expressing TH and β2-AR was altered in arterial hypertension and can be modulated by central sympathetic inhibition with clonidine treatment.